Assessment of The Various Type of Mangrove Areas by Avifaunal Diversity and Community in Tamban Beach, Sumbermanjing Wetan, East Java - Agus Nurrofik; Achmad Dadang Burhanuddin; Lutfita Fitriana; Luchman Hakim; Nia Kurniawan (Biotropika: Journal of Tropical Biology, 2021)
The restoration effort in Tamban Beach may reflect the role services of mangroves as suitable habitats for those surrounding diversity, especially on avifauna. Here we assess the diversity and community of avifaunal throughout types of mangrove ecosystems. We surveyed the avifaunal within four stations (i.e., natural mangrove area, restored mangrove area since 2009 and 2014, and degraded mangrove area) in Tamban Beach, Sumbermanjing Wetan, East Java during March 2021 using Audiovisual Encounter Survey (AES) methods. We present the statistic descriptive analysis of α-diversity index (taxa diversity, dominance index, Simpson’s index, Evenness, Shannon-Wiener diversity index, Brillouin index, and Margalef species richness) as diversity assessment also conservation status of each species. The Principal Component Analysis (PCA) was performed to investigate the community variation within each site. We found 38 species from 22 families and 11 orders of avifaunal across the sites. The diversity of avifauna was high in a degraded area due to the mixture of habitats, although the natural and restored area yields some specialists. The type of mangroves might not be the sole factor affecting the avifauna diversity correlation, highlighting the importance of conservation strategies in the area.